A Qualitative Thematic Analysis of Online Mental Health Resources for Oklahoma's Agriculturalists - Kelsee Dale; Quisto Settle; Dwayne Cartmell; Shelly Legg (Journal of Applied Communications, 2025)
In the center of Oklahoma's agricultural landscape is an ongoing struggle: the mental health of its farmers and ranchers. Farming is a unique occupation that requires specific mental health needs tailoring to their way of life. Existing literature highlights the elevated risk of mental health disorders and suicide among farmers, underscoring the urgency of understanding and addressing mental health issues within agricultural communities. This study utilized thematic analysis to explore the array of mental health resources available to Oklahoma's agricultural community by analyzing both textual and visual material. Six major themes were found throughout the content of existing mental health resources for Oklahoma agriculturalists. The major themes included causes of stress, stress management, how to have uncomfortable conversations, warning signs, emotional intelligence, and support. The findings of this study offer guidance for the development of future resources aimed at addressing the mental health needs within Oklahoma's agricultural communities. Future campaigns should ensure specific behaviors are targeted, along with collaborating between organizations when possible to increase reach of campaigns. Future research is needed to understand the impacts of social marketing efforts to promote mental health behaviors of agriculturalists.
Keywords: rural; mental health; social marketing